High false negative rate of frozen section examination of sentinel lymph nodes in patients with cervical cancer - Slama, J.; Dundr, P.; Dusek, L.; Cibula, D. (Gynecologic oncology, 2013)
Metastatic involvement of the sentinel nodes (SN) is one of the main prognostic factors in cervical cancer which determines the disease management. The results of intra-operative SN examination would make it possible to triage patients in a one-step protocol. The studies carried out on the subject so far have, however, failed to demonstrate adequate accuracy of frozen section examination (FS) and, moreover, they only involved small cohorts. The study included 225 patients with cervical cancer FIGO IA2–IIB in whom at least one SN has been detected and intra-operatively processed. The prevalence of macrometastases, micrometastases and isolated tumour cells (ITC) in the SN was evaluated and the results of FS and final SN ultrastaging were compared. Metastatic involvement of the SN was detected by pathologic ultrastaging in 73 cases (32.4%); macrometastases, micrometastases and ITC were found in 48, 17 and 8 patients, respectively. Intra-operative SN assessment established the SN status correctly in as few as 41 cases (56.2%), or in 49 cases (63%) if ITC had been excluded. Final ultrastaging of intra-operatively negative SN confirmed macrometastases, micrometastases, and ITC in additional 8, 18 and 8 patients, respectively. The false negative rate of FS was higher in bigger tumours (>20cm3) and in the presence of LVSI. Frozen section examination of SN is not sufficiently reliable; it has a high false negative rate mainly due to its limited ability to detect micrometastases. A possible solution would be a more detailed intra-operative pathologic processing or two-step surgical management. ► Intra-operative frozen section examination of sentinel nodes yielded a false negative result in almost half of the cases (44%). ► The sensitivities for diagnosing macrometastases and low-volume disease (micrometastases and isolated tumour cells) were 81% and 8%, respectively. ► False negative rate of frozen section was higher in bigger tumours (>20cm3) and in the presence of LVSI.